Adolescent with Prader-Willi Syndrome, superobesity, and associated comorbidities: clinical and therapeutic challenges in a case report (Brazilian Journal of Health Research, 2024)
Introduction: Prader-Willi Syndrome (PWS) is the most common syndromic form of obesity, caused by the absence of the expression of paternally active genes on chromosome 15q11.2-q13. Its features include hyperphagia, early-onset obesity, hypogonadism, developmental delay, behavioral changes, and characteristic facial traits. Neonates typically present with hypotonia and feeding difficulties. Case Report: A 15-year-old patient diagnosed with PWS through the absence of the paternal allele. Since the first year of life, the patient presented an ascending weight curve, leading to superobesity, hypertension, diabetes, and sleep apnea. The patient also developed anxiety disorders, depression, severe food compulsions, and mobility difficulties. During hospitalization, nutritional control, behavioral therapy, and continuous positive airway pressure (CPAP) were initiated. Conclusion: Comorbidities associated with PWS require integrated multidisciplinary management. The patient’s superobesity was exacerbated by poor therapeutic adherence and familial challenges in managing hyperphagia, highlighting the importance of personalized interventions to improve quality of life.
Keywords: Pediatrics; Adolescence; Prader-Willi Syndrome; Obesity; Multidisciplinary